Nude Venus: nudity between modesty and horror - Daniela Queiroz Campos; Maria Bernardete Ramos Flores (Revista Brasileira de Estudos da Presença, 2018)
The text analyses the Renaissance corporal construction approached, over all, in the works of two art historians: Aby Warburg and Georges Didi-Huberman. Sandro Botticelli's paintings are presented as images motto. The study departs from the impenetrable white body of the Birth of Venus and problematizes the horror of the image, apparently only marked by modesty. Warburg and Didi-Huberman discuss the Dionysian pathos in the image from the mythical texts of Homer and Poliziano. Lastly, it is discussed the image of the Story of Nastagio degli Onesti with the purpose of considering the open body concealed by the enclosed body in the Italian Renaissance of the arts.